Prevalence and epidemiological distribution of substance use among people living with HIV in the East African region: a meta-analysis - Onohuean, Hope; Onohuean, Fanny Eseohe; Omara, Charles; Saleem, Haneefa (Frontiers in Psychiatry, 2025)
BackgroundThe East African region lacks synthesised scientific evidence on the impact of different substances used on HIV management and treatment outcomes in this population. We meta-analysed epidemiological data on substance use among people living with HIV to determine the regional estimate of the prevalence, associated factors, and changes over time for each gender, per year or age.MethodThe documents were obtained via electronic databases following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines.ResultsThe 53 studies from the East African region showed a pool estimate proportion of 60.36%, 95% confidence interval (CI) (0.5301–0.6728) with an I2 = 98.88% using the random-effects model, and Q-statistic (df = 52) = 4,662.95, p < 0.0001. The publication bias is revealed by funnel plots, 55.15%, CI (0.4637–0.6362); Egger’s linear regression test indicates z = 12.6415, p < 0.0001; and the rank correlation test of Kendall’s tau = 0.1011, p = 0.2955. The subgroup analysis showed an estimate of the study type: cohort, 66.10%, CI (0.5672–0.7437), I2 = 98.60%, and cross-sectional, 58.98%, CI (0.4009–0.7555), I2 = 99.06%. The variables of the subgroup analysis by study size indicate the following: >1,000 sample size, 76.05%, CI (0.4661–0.9203), I2 = 99.75%, and <1,000 sample size, 62.85%, CI (0.5396–0.7095) I2 = 100%. The meta-regression analysis of heterogeneity indicates that the covariate of countries (R2 = 0.00%, p < 0.0001), types of substance use (R2 = 0.00%, p < 0.0001), and study period (R2 = 16.95%, p = 0.0013) significantly moderate the observed heterogeneity.ConclusionThe East African region has a high prevalence of substance use among people living with HIV, which may further increase the risk of spread of infections and signs of deteriorating physical and mental health. Comprehensive treatment and establishing interventions for substance abuse/misuse among people living with HIV could be a top health priority in the region.